Comparative Study of Ocular Pharmacokinetics of Gatifloxacin Between Continuous Lavage and Hourly Topical Instillation in Rabbits. Issue 11 (November 2018) - Zhao, Xin; Shen, Xu; Zhang, Xian; Chen, Shichao; Lu, Hong; Wang, Mingwu
Abstract : Purpose: To investigate the ocular pharmacokinetics and distribution of gatifloxacin between continuous lavage through the Morgan lens and repeated topical drop instillation in rabbits. Methods: Thirty-six healthy rabbits were randomly divided into 2 groups, and 0.3% gatifloxacin ophthalmic solution was instilled by continuous lavage using the Morgan lens onto the left eyes at 15 mL/h (or 50 μL of the same solution repeatedly administered topically every hour). The animals were killed at 2, 4, 8, and 12 hours in the Morgan lens group or at 12 and 24 hours in the topical instillation group. Aqueous humor specimens were collected from the anterior chamber first, and other ocular tissues and plasma were collected subsequently. Pharmacokinetic and pharmacodynamic indices, other than the minimum inhibitory concentration (MIC), were used as therapeutic parameters in ocular tissues. Results: The highest concentration was found in the corneas in both groups. With continuous lavage, gatifloxacin reached an efficacious high concentration in 4 hours in the cornea, which is equivalent to about 23 times the concentration reached in the same tissue by hourly topical instillation for 12 to 24 hours. Using historic data as references, C/MIC90 was 105 (>10) and AUC0–t /MIC90 was 194 h (>125) in the cornea in the continuous lavage group at 4 hours, whereas these values were 5 and 73 hours for the topical hourly instillation group. Conclusions: Compared with hourly topical instillation, continuous lavage through the Morgan lens could achieve significantly higher concentrations in ocular tissues within a short period, especially in the cornea. Continuous lavage may be a much more efficient way to treat recalcitrant corneal infections.